Analysis of a government policy to address nursing shortage and nursing education quality - Abhicharttibutra K. (2017)
© 2016 International Council of Nurses Background: A well-educated, sufficient nursing workforce improves population health and standards of nursing care. Analysing workforce policies assists nurses to learn from the past and develop better future policies. Aim: Describe policy-making processes in the first Thai government plan to increase nursing capacity and improve nursing education quality. Design: A qualitative study employing Longest's model to examine policy-making processes. Methods: Data were obtained from 28 in-depth interviews with key informants, who had been committee members and former deans of nursing involved with the policy processes in the 1990s. Both qualitative and quantitative data were extracted from relevant documents, and content analysis employed with all data. Findings: Three policy phases were identified. Policy formulation, where three streams of problems, politics and policy resulted in identification of nursing shortage, changes of government incumbents and needing to increase nurse production; Policy implementation included creating methods of implementation, appointing responsible people and committees, creating operational plans, producing more nurses and faculty development projects and Policy modification which incorporated implementing the first Thai international doctoral degree in English, a collaborative programme between universities. Study limitations: Not all key informants could be accessed due to the passage of time. Findings are unique to Thailand but inform internationally of nurses’ abilities and need to be involved in policy. Conclusion: Nurses were involved in all policy phases. While the policy produced positive developments in growing nursing capacity and education in the past, nursing shortages remained and are now acute in Thailand. Implications for Nursing/Health Policy: Lessons learned from this policy analysis help explain why the nursing education and nursing shortage policy was legislated through the government agenda, and the active involvement of Thai nurses in this process. Nurses globally need to be at the policy-making table to try to reduce nursing shortages, and enhance practice and education environments.